Statistical optimization of cellulase biosynthesis by isolated cellulolytic fungi utilizing horticultural waste - Mandal, Modhuleena; Ghosh, Uma (Acta Biologica Szegediensis, 2016)
Cellulase production by isolated cellulolytic fungi was carried out by utilizing horticultural waste, banana peel under solid state fermentation (SSF). The isolated fungus was previously tested for its cellulose hydrolyzing ability by observing the clear zone pattern around the colonies on CMC amended agar plates followed by secondary screening on wheat bran. The isolate named SS3 (5) that exhibited maximum enzyme activity at the level of 19.9 U/gds and 3.7 U/gds for CMCase and FPase respectively was chosen for further morphological and genotypic identification. The isolate was found to be similar to Aspergillus niger isolates, based on 18S rRNA sequencing and BLAST analysis. Statistical optimization of cellulase biosynthesis by the addition of nutritional supplements to a banana peel based medium was studied by response surface methodology (RSM) involving Box-Behnken Design (BBD), which resulted in an improved cellulase yield. The cellulase production was found to be increased by 2.01-fold and 1.4-fold for CMCase and FPase, respectively, under statistically optimized nutritional conditions (i.e. medium supplemented with 0.06% MgSO4, 0.4% Triton X-100 and 0.52% NaNO3) compared to the control (i.e. medium without supplements).